2019
DOI: 10.3389/fonc.2019.00316
|View full text |Cite|
|
Sign up to set email alerts
|

The Profile of Immunophenotype and Genotype Aberrations in Subsets of Pediatric T-Cell Acute Lymphoblastic Leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is a biologically heterogeneous malignancy, which reflects distinctive stages of T-cell differentiation arrest. We have revisited a cohort of pediatric T-ALL, in order to test if immunophenotypes associated with molecular alterations would predict the patient's outcome. Genetic mutations, translocations and copy number alterations were identified through Sanger sequencing, RT-PCR, FISH and multiplex ligation-dependent probe amplification (MLPA). We defined 8 immunoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
6
34
0
2
Order By: Relevance
“…Similar concomitance between particular gene deletions (WT1, IFNA, RB1, and CTCF) was previously reported by Zhang et al (51). We did not observe the co-occurrence between SUZ12 and CDKN2AB alterations, although Noronha et al (4) indicate such concomitance in their study. The study of Karrman et al (15) revealed that CDKN2A deletions were significantly associated with a high WBC count, but we did not find a similar association in our cohort.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar concomitance between particular gene deletions (WT1, IFNA, RB1, and CTCF) was previously reported by Zhang et al (51). We did not observe the co-occurrence between SUZ12 and CDKN2AB alterations, although Noronha et al (4) indicate such concomitance in their study. The study of Karrman et al (15) revealed that CDKN2A deletions were significantly associated with a high WBC count, but we did not find a similar association in our cohort.…”
Section: Discussionsupporting
confidence: 90%
“…The lack or reduced expression of RUNX1 also affects the activity of MYB, MYC , and GATA3 oncogenes, which confirms the key role of RUNX1 in the pathogenesis of T-ALL ( 24 ). In the described cohort of patients, RUNX1, MYB , and GATA3 changes affected 8.1% ( n = 7), 12.8% ( n = 11), and 1.2% ( n = 1) of cases, respectively, which corresponds to the results that have been previously reported ( 4 , 9 , 25 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Unique gene expression profiles were later found to be associated with leukemic arrest of thymocytes at different developmental stages [ 15 ], leading to the definition of new T-ALL subgroups characterized by the driver oncogenes or oncogene fusions ( TAL/LMO, TLX1, TLX3 , HOXA , and MYB genes), denoted as type A aberrations, present at diagnosis [ 16 ]. Other genetic alterations, denoted as type B, are recurrently detected in T-ALL patients and include point mutations, insertions and deletions (INDELs), and chromosomal gains or losses, which result in activation of the NOTCH1 T-cell fate specification pathway ( NOTCH1/FBXW7 ) in more than 60% of T-ALL cases [ 17 ], activation of cytokine signaling pathways ( IL7R, JAK1/3, FLT3, CKIT, PI3K/AKT/PTEN, ABL1, N/KRAS ) and transcription factors ( RUNX1, ETV6, BCL11B, WT1, TCF7, LEF1, CTNNB1, GATA3, IKZF1 ), inactivation of cell cycle inhibitors ( CDKN2A/B, CDKN1B, CDKN1C, CCND3, RB ), or deregulation of chromatin modifiers and remodeling factors ( PHF6 , CTCF, KDM6A, SETD2, KMT2A/2D/2C, DNMT3A, IDH1/2 ) (reviewed in [ 18 , 19 , 20 , 21 , 22 ]).…”
Section: Introductionmentioning
confidence: 99%